Enoxaparin Dose Requirements to Achieve Therapeutic Low–molecular-weight Heparin Anti-factor Xa Levels in Infants and Young Children. Issue 7 (October 2021) - Wysocki, Emma L.; Kuhn, Alexis; Steinbrenner, Jenny; Tyrrell, Laura; Abdel-Rasoul, Mahmoud; Dunn, Amy; Cloyd, Colleen
Abstract : Introduction: Enoxaparin is commonly used to treat pediatric thrombosis. Several small retrospective studies have suggested that infants and young children require higher enoxaparin doses to achieve therapeutic anti-factor Xa levels compared with adults. Materials and Methods: This is a retrospective study of hospitalized children who received enoxaparin for the treatment of thrombosis at a free-standing children's hospital. The primary objective was to ascertain the enoxaparin dose required to achieve an anti-factor Xa level of 0.5 to 1.0 U/mL among 4 age groups in a large cohort of infants and young children between 60 days and 5 years of age. Results: A total of 176 infants and children were evaluated. The majority of patients were less than 1 year of age (n=104). An inverse relationship between enoxaparin dose needed to achieve therapeutic anti-factor Xa levels and patient age was noted, particularly in the first year of life. Patients who were 60 days to less than 7 months at the time of enoxaparin initiation (n=73) required the highest mean dose among the age groups at 1.73 mg/kg subcutaneously every 12 hours ( P <0.0001). Conclusion: Infants and young children require higher doses of enoxaparin to achieve therapeutic anti-factor Xa levels compared with adults.